2011
DOI: 10.1155/2011/542695
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Remodeling of the Umbilical Cord in Pre-eclampsia as a Risk Factor for Fetal Hypertension

Abstract: The human umbilical cord forms a connection between the placenta and the foetus. It is composed of two arteries and one vein surrounded by Wharton's jelly. Pre-eclampsia is accompanied by extensive remodeling of extracellular matrix of umbilical cord. Matrix metalloproteinases (MMPs) are engaged in degradation of extracellular matrix proteins and activation/inactivation of certain cytokines and enzymes. These enzymes will probably play a central role in the release of matrix-embedded cytokines and growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…ECM was a dynamic fibrous protein network with mutual interaction between the big molecules, which contained collagen, mucin, fibronectin, proteoglycan, etc. MMPs family was one of the most vital proteases, which could degrade ECM [5]. The degradation of ECM was the key stage of tumor metastasis, mainly under the regulation of MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…ECM was a dynamic fibrous protein network with mutual interaction between the big molecules, which contained collagen, mucin, fibronectin, proteoglycan, etc. MMPs family was one of the most vital proteases, which could degrade ECM [5]. The degradation of ECM was the key stage of tumor metastasis, mainly under the regulation of MMPs.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are not in agreement those reported by Kolben et al [111] and Shokry et al [112], who observed reduced immunologically defined MMP-9 levels in preeclamptic placental tissues collected at delivery. In addition, Galewska et al used distinct techniques to show that preeclamptic umbilical cord tissues (artery and vein) had lower MMP-2 and MMP-9 levels than healthy tissues [113]. However, they found increased MMP-9 levels in plasma obtained from umbilical cord blood samples from preeclamptic newborns, and no significant differences in MMP-2, TIMP-1 and TIMP-2 compared with those measured in healthy pregnancies [114].…”
Section: Clinical Findings Showing Mmp Alterations In Preeclampsiamentioning
confidence: 99%
“…Women with GH more often present a decrease in the umbilical cord length than women without it (13) . However, our data indicate that women with GH (82.8%) and GDM (82.1%) had a higher frequency of umbilical cord measuring between 36 and 70 cm.…”
Section: Discussionmentioning
confidence: 95%